THE ROLE OF ICT IN MASSIVE OPEN ONLINE COURSES - Zohirov, Sh. (SCIENCE and SOCIETY, 2023)
This article focuses on the role of ICT in MOOC (Massive Open Online Courses), using ICT for teaching represents a wide range of new opportunities and possibilities and some reasons for TELL (Technology Enhanced Language Learning).